Pengembangan Website Bus Listrik Medan dengan Fitur Pengaduan dan Jadwal Keberangkatan Menggunakan Metode Prototype - Amira Salsabila; Muhammad Irwan Padli Nasution (CV. Multi Kreasi Media, 2026)
The unstructured provision of schedule information and places to submit complaints in public transportation is often a major problem for passenger satisfaction. The purpose of this research is to create an easy-to-use website-based information system regarding schedules and complaints for Medan Electric Buses. The method used in the development is the Prototype Method, which focuses on gradual improvements and rapid user assessments to ensure all requirements are functioning properly. The development process consists of several stages, starting from determining needs, designing the system (using UML), building a prototype, to starting (Customer Evaluation). The results of the implementation of the main features Departure Schedule and Complaint Form show that this system has been operating according to the predetermined plan.